AI Assistance and Its Advantages in Language Learning (FAN, TA’LIM, TEXNOLOGIYA VA ISHLAB CHIQARISH INTEGRATSIYASI ASOSIDA RIVOJLANISH ISTIQBOLLARI, 2024)
The great advancement of technology has made its impact on every sphere of our lives and education is an outstanding example of this modification. Artificial intelligence possesses a great influence in terms of language learning offering the chances of personalized approach and many other merits which are analyzed in this very article.